Hypertriglyceridemic waist circumference and its association with arterial hypertension in a sample of Peruvian adult population: Cintura hipertrigliceridémica y su asociación con la hipertensión arterial una muestra de pobladores adultos peruanos - Vera-Ponce, Víctor J. (2021)
Objective: To evaluate the prevalence of hypertriglyceridemic waist (HTGW) and its association with arterial hypertension (AHT) in Peruvian adults. Methodology: Cross-sectional analytical study of the secondary database from the "National Survey of Nutritional, Biochemical, Socioeconomic and Cultural Indicators related to Chronic-Degenerative Diseases". HTGW was measured according to the presence of hypertriglyceridemia (≥ 150 mg/dl) and increased abdominal waist, according to JIS (men ≥ 94 cm and women ≥ 80 cm) and ATPIII (men ≥ 102 cm and women ≥ 88 cm) criteria. Results: the prevalence of AHT was 12.48%, HTGW -JIS was 21.49%, and HTGW-ATPII was 13.96%. In multiple regression, HTGW-JIS showed that they had 1.35 higher frequency of having AHT versus those without HTGW (PR=1.35; CI95%: 1.13 - 1.61; p = 0.001) and HTGW-ATPIII showed that they had 1.38 higher frequency of having AHT versus those without HTGW (PR=1.38; CI95%: 1.14 - 1.67; p = 0.001), both adjusted for convenience variables. Conclusion: HTGW was positively associated with AHT.